Expansion of Foxp3+ T‐cell populations by Candida albicans enhances both Th17‐cell responses and fungal dissemination after intravenous challenge. Issue 4 (13th February 2014) - Whibley, Natasha; MacCallum, Donna M.; Vickers, Mark A.; Zafreen, Sadia; Waldmann, Herman; Hori, Shohei; Gaffen, Sarah L.; Gow, Neil A. R.; Barker, Robert N.; Hall, Andrew M.
<x xml:space="preserve">Abstract</x> Candida albicans remains the fungus most frequently associated with nosocomial bloodstream infection. In disseminated candidiasis, the role of Foxp3+ regulatory T (Treg) cells remains largely unexplored. Our aims were to characterize Foxp3+ Treg‐cell activation in a murine intravenous challenge model of disseminated C. albicans infection, and determine the contribution to disease. Flow cytometric analyses demonstrated that C. albicans infection drove in vivo expansion of a splenic CD4+Foxp3+ population that correlated positively with fungal burden. Depletion from Foxp3hCD2 reporter mice in vivo confirmed that Foxp3+ cells exacerbated fungal burden and inflammatory renal disease. The CD4+Foxp3+ population expanded further after in vitro stimulation with C. albicans antigens (Ags), and included at least three cell types. These arose from proliferation of the natural Treg‐cell subset, together with conversion of Foxp3− cells to the induced Treg‐cell form, and to a cell type sharing effector Th17‐cell characteristics, expressing ROR‐γt, and secreting IL‐17A. The expanded Foxp3+ T cells inhibited Th1 and Th2 responses, but enhanced Th17‐cell responses to C. albicans Ags in vitro, and in vivo depletion confirmed their ability to enhance the Th17‐cell response. These data lead to a model for disseminated candidiasis whereby expansion of Foxp3+ T cells promotes Th17‐cell responses that drive pathology.